'My 30 Years Life as a Litigator' by the founder and managing partner of Messrs. Thomas Philip, Advocates & Solicitors - UiTM, Faculty of Law (Faculty of Law, 2022)
The F acuity of Law. UiTM, through Sekretariat Mahasiswa Fakulti Undang-Undang (SMF). had organized 'A Talk: My 30 Years' Life as a Litigator' with the renowned Mr. Mathew Thomas Philip. Founder and Managing Partner of Messrs. Thomas Philip. Advocates & Solicitors. Mr Mathew shared his vast experiences in the legal industry, from when he counselled and represented numerous domestic and international clients in civil and commercial litigation. The talk, held on 28 October 2022, was attended by Part 8 students of UiTMLaw, who will be graduating soon and entering the job market. Throughout the program, Mr Mathew talks of the lessons he learnt from conducting myriads of trials and handling clients from all walks of life. He stresses the importance of networking. even while they are still studying, as the connections made will fast for a lifetime.